2020
DOI: 10.3389/fphar.2020.00739
|View full text |Cite|
|
Sign up to set email alerts
|

Increased Appetite Plays a Key Role in Olanzapine-Induced Weight Gain in First-Episode Schizophrenia Patients

Abstract: Weight gain and metabolic disturbances, potentially influenced by increased appetite, are common effects of olanzapine treatment in patients with schizophrenia. In this study, we explored the association between olanzapine-induced weight gain and metabolic effects with increased appetite. Drug-naïve, first-episode schizophrenia patients were treated with olanzapine for 12 weeks. Assessments included time to increased appetite, body weight, body mass index, biochemical indicators of blood glucose and lipids, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…In the present study, female rats were used since previous studies have reported that olanzapine treatment induced hyperphagia and weight gain in female rats but not in male rats (Baptista et al, 2002;Pouzet et al, 2003;Arjona et al, 2004). Moreover, clinical studies have shown that female patients were more likely to gain weight compared with males under olanzapine treatment (Bobes et al, 2003;Andersen et al, 2005;Saddichha et al, 2007;Huang et al, 2020). Therefore, in the present study, female rats were used to mimic olanzapineinduced weight gain in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, female rats were used since previous studies have reported that olanzapine treatment induced hyperphagia and weight gain in female rats but not in male rats (Baptista et al, 2002;Pouzet et al, 2003;Arjona et al, 2004). Moreover, clinical studies have shown that female patients were more likely to gain weight compared with males under olanzapine treatment (Bobes et al, 2003;Andersen et al, 2005;Saddichha et al, 2007;Huang et al, 2020). Therefore, in the present study, female rats were used to mimic olanzapineinduced weight gain in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…14,17 Data have also emphasized on behavioural mechanisms such as appetite changes following olanzapine initiation. 18,19 Regarding potential predictors of olanzapine-related weight gain, some evidence suggests that patients with larger early weight gain (EWG) (weight gain within 2 weeks after olanzapine initiation) may be at higher risk of olanzapine-induced weight gain. 20 The predictive role of EWG changes for the long-term weight gain was also reported in a 1-year longitudinal study of inpatients.…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic drugs are prescribed as a main treatment that alleviates symptoms, prevents relapse of schizophrenia, and regulates the dopamine level to the normal. However, usage of antipsychotic drugs often has the side effects of increasing appetite and body weights by interfering ghrelin and leptin, so disturbance of dopaminergic neurotransmission may change food intake and increase body weight in schizophrenia population [ 9 10 11 ]. Also, schizophrenia patients had poor dietary patterns with more saturated fats, sugar and alcohol as well as less intakes of fish, vegetables, and fruits, which may be related to impaired cognitive function [ 12 13 ].…”
Section: Introductionmentioning
confidence: 99%